A Study of Restorative Justice in Cases of Minor Assault - Kemas Adhitya Luthfi; Alip Rahman; Anom Sutrisno (Journal of Social Research, 2026)
This study investigates the implementation of restorative justice in minor assault cases at the Cirebon Police Department, Indonesia, within the broader context of a global shift in criminal justice from retributive punishment toward reconciliation and social repair. Minor assaults are prevalent, yet conventional punitive approaches often fail to address the social and relational harm caused by such offenses. Restorative justice offers an alternative by emphasizing victim recovery, offender accountability, and community cohesion. The study aims to analyze how restorative justice is applied in practice, identify supporting and inhibiting factors, and evaluate its effectiveness in resolving minor assault cases. The research employs an empirical legal approach with a qualitative, socio-legal methodology. Primary data were obtained through in-depth interviews and direct observations of police practices, while secondary data included legal regulations, internal policies, and previous studies on restorative justice. Findings reveal that police discretion plays a critical role in determining case suitability, initiating mediation, and facilitating dialogue between victims and perpetrators. Successful implementation depends on victim willingness, offender accountability, and case severity, whereas inconsistencies arise from the absence of technical guidelines and the prevalence of punitive mindsets. The study concludes that restorative justice effectively resolves minor assaults by restoring social relationships and promoting accountability. However, standardized procedures, officer training, and public education are necessary to ensure its consistent and equitable application.